Hubungan Stres dengan Kejadian Irritable Bowel Syndrome pada Mahasiswa Tahun Pertama Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Komang Rossa Triana Kusumadewi; Luh Gede Sri Yenny; A.A. Sri Agung Aryastuti (Aesculapius Medical Journal, 2022)
Faculty of Medicine has a variety of learning methods that can cause stress which can trigger a functional disorders in the digestive tract, namely irritable bowel syndrome (IBS). This research aims to determine the relationship between stress and the incidence of IBS in first year students of the Faculty of Medicine and Health Sciences, University of Warmadewa. This research was conducted from February to March 2022 using a cross-sectional study and simple random sampling technique. The subjects of this study were students of the Faculty of Medicine and Health Sciences, University of Warmadewa batch 2021 who met the inclusion and exclusion criteria, totaling 73 people. The instruments in this study were the Rome IV questionnaire for the incidence of IBS and the Perceived Stress Scale (PSS) questionnaire for stress levels. Data analysis in this research is Mann-Whitney test with a p value that considered significant, namely <0.05. Based on this study, the prevalence of mild stress was 9 people (12.3%), moderate stress was 61 people (83.6%), and severe stress was 3 people (4.1%). The prevalence of irritable bowel syndrome was 7 people (9.6%). Through the Mann-Whitney analysis, a significant p value of 0.015 (p<0.05) was obtained. The results showed that there was a relationship between stress and the incidence of IBS in first year students of the Faculty of Medicine and Health Sciences, Warmadewa University. Medical students are advised to care and be aware of the symptoms and body conditions that can occur due to stress.